2015
DOI: 10.1111/age.12344
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations in the amylase gene (AMY2B) in Japanese native dog breeds

Abstract: A recent study suggested that increased copy numbers of the AMY2B gene might be a crucial genetic change that occurred during the domestication of dogs. To investigate AMY2B expansion in ancient breeds, which are highly divergent from modern breeds of presumed European origins, we analysed copy numbers in native Japanese dog breeds. Copy numbers in the Akita and Shiba, two ancient breeds in Japan, were higher than those in wolves. However, compared to a group of various modern breeds, Akitas had fewer copy num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…The effective population size in wolves is higher than that in dogs so higher genome diversity in wolves is expected compared to dogs [3,25]. Our results from two components of genetic variation sources including SVs and CNVs confirmed that the novel adaptations permitted the primal ancestors of recent dogs to live on a diet high starch compared to the carnivorous diet of wolves and formed a essential step in the primal domestication of dogs [8,9,25,52,60]. The terms "Negative regulation of neuron apoptotic process", "positive regulation of dendrite development" and "nervous system development" were enriched among SVs in wolf and are indicative of reducing aggression in the first steps of animal domestication.…”
Section: Discussionsupporting
confidence: 60%
“…The effective population size in wolves is higher than that in dogs so higher genome diversity in wolves is expected compared to dogs [3,25]. Our results from two components of genetic variation sources including SVs and CNVs confirmed that the novel adaptations permitted the primal ancestors of recent dogs to live on a diet high starch compared to the carnivorous diet of wolves and formed a essential step in the primal domestication of dogs [8,9,25,52,60]. The terms "Negative regulation of neuron apoptotic process", "positive regulation of dendrite development" and "nervous system development" were enriched among SVs in wolf and are indicative of reducing aggression in the first steps of animal domestication.…”
Section: Discussionsupporting
confidence: 60%
“…The effective population size in wolves is higher than that in dogs so higher genome diversity in wolves is expected compared to dogs [3,30]. Our results from two components of genetic variation sources including SVs and CNVs confirmed that the novel adaptations permitted the primal ancestors of recent dogs to live on a diet with high starch compared to the carnivorous diet of wolves, which is an essential step in the primal domestication of dogs [9,10,30,64,73]. The term "nervous system development" was enriched among SVs in wolf and is indicative of reducing aggression in the first steps of animal domestication [70].…”
Section: Discussionsupporting
confidence: 60%
“…The effective population size in wolves is higher than that in dogs so higher genome diversity in wolves is expected compared to dogs [3,29]. Our results from two components of genetic variation sources including SVs and CNVs confirmed that the novel adaptations permitted the primal ancestors of recent dogs to live on a diet with high starch compared to the carnivorous diet of wolves, which is an essential step in the primal domestication of dogs [8,9,29,60,69]. The term "nervous system development" was enriched among SVs in wolf and is indicative of reducing aggression in the first steps of animal domestication [66].…”
Section: Discussionsupporting
confidence: 54%